Exploring Vocational Interest Measurement Instruments in Indonesia: Insights from a Scoping Review - Bagaskara, Rafli Sodiq; Nurochim, Hanif Firdaus Gitya Iman; Susilowati, Hadina Pramesti Diba; Agustin, Nisrina Nurika (Faculty of Psychology, Universitas Gadjah Mada, 2024)
The difficulty of finding vocational interest measurement tools with good psychometric properties and relevance to modern developments is a current concern in Indonesia. Therefore, this scoping review aims to compile a list of vocational interest measurement tools available in Indonesia that have been psychometrically tested. For this purpose, a total of 2,196 articles were extracted from the Google Scholar, Garuda, and Scopus databases. The article selection procedure followed the PRISMA-ScR flow diagram, and the screening process resulted in 17 sample articles (2014–2024). The analysis showed that most vocational interest measurement tools in Indonesia use a top-down development approach, based on Holland’s Structure of Interests, and emphasize internal structure validity and internal consistency reliability as the tested psychometric properties. Further research is needed to address the gaps in validity evidence that remain among Indonesian vocational interest measurement tools.